Evaluation of Antimicrobial Efficacy Against E. coli Isolates of Different Serogroups Obtained from Diarrhoeic Neonates of Calves, Kids, and Lambs - R Pachaury; A K Kataria (Media Peternakan, 2012)
Fourteen antimicrobials were evaluated their efficacy against 115 Escherichia coli isolates recovered from faecal samples collected from neonatal diarrhoeic calves (66), kids (25) and lambs (24).  Of these isolates 37 were nontypeable, four were of rough type and 74 isolates were typeable for 'O' antigen belonging to 19 different serogroups (O2, O3, O5, O17, O21, O22, O25, O41, O45, O55, O60, O65, O70, O76, O114, O116, O147, O152, and O158). Evaluation of antimicrobial efficacy by disc diffusion method revealed that the most effective antibiotics were ciprofloxacin, sparfloxacin and triple sulpha followed by co-trimoxazole, chloramphenicol, nitrofurantoin, gentamicin, nalidixic acid, polymixin-B and amoxyclav in decreasing order of their efficacy while ampicillin and cephotaxime were found totally ineffective against these isolates. All the isolates showed multiple drug resistance to various antibiotics ranging from two to ten antibiotics. The resistance patterns were independent of serogroups of isolates and the animal species from which isolates were obtained. However, there was a variation in resistance pattern for same antibiotic vis-a vis locations of their isolation.